Investigative modelling of the flood bypass channel in Kuching, Sarawak, by assessing its impact on the inundations of Kuching-Batu Kawa-Bau Expressway - Mah, Yau Seng; Lai, S.H.; Chan, R.A.@R.B.; Putuhena, F.J. (Taylor & Francis Group, 2012)
Flood risks not only include loss of human lives and properties, but also the transportation and communication. One major road in Kuching, the Kuching-Batu Kawa-Bau Expressway is often flooded and interrupted by floodwaters from Sarawak River. The Sarawak State Government had announced to build a flood bypass channel in Sarawak River to mitigate flood under the Ninth Malaysian Plan. This paper is a study on the effects of the structure in the flooding of the mentioned road stretch. The January 2004 event which is locally known as a 100-year flood, was run through a developed river model incorporated with the bypass facilities. The model had indicated a reduction of 53% of flooded road. Similarly, modelling of 10 and 50-year design floods had predicted over 50% of reduction. The bypass channel was said to be able to alleviate the flooding on the major road stretch.